Activity pattern, energy expenditure and energy intake among male athletes during a training and no training days - Wan Nudri Wan Daud (Tanjong Malim, 2022)
Activity pattern, energy expenditure and energy intake among male athletes during a training and no training days by Wan Nudri Wan Daud